KINETIKA REAKSI PEMUNGUTAN KHROM DALAM LIMBAH CAIR PENYAMAKAN KULIT DENGAN KAPUR PADAM DALAM REAKTOR ALIR TANGKI BERPENGADUK (RATB) (Reaction Kinetics of Chrom removal from Tanning Liquid Waste with Lime in a Stirred Tan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Liquid waste of tanning industry containing chromic ions, is very dangerous to people and damaging soil quality. Therefore, before it could be released to the environment, the liquid waste has to be treated to reduce its chromic content to the allowable value. hi this research the liquid waste was reacted with lime powder in a Stirred Tank Flow Reactor (STFR). Samples were taken from the products periodically and after being separated from the solid, the chromic ion contents left in the liquid were analyzed using the Atomic Absorption Spectrophotometer_ The solid product containing the chromic hydroxide was treated with sulfuric acid solution to recover the chromic compound. The result showed that the chromic ion could be removed quite well from the liquid waste with lime powder of almost stoichiometric quantity. The reaction proceeded homogeneously. The influences of the radius of solid and initial concentration of the chromic ion in the liquid waste were neglected. The rate of reaction increased with temperature and the rate constant could be expressed as: k0 = 461,6468e (-2483'9487AT) The relative favorable process conditions were liquid waste containing 4.000 ppm of chromic ion 300 K, 0.0106 cm of particle diameter, and 60 minutes of reaction time. Under these conditions, the chromic ion left was lower than the allowable value (2 ppm). The recovery of chromic ion from the solid product of treatment was 66.71 %.